The Pathways to Nurturing Children’s Growth Mindset in Family Education - Lin Liu; Yong Liu; Lei Wang; Chenghai Gao; Tao Wang (Journal of Advanced Research in Education, 2024)
In family education, both parents and children have a belief system to construct the world and interpret experience. Some of these beliefs point to a dynamic self and a dynamic world with the possibility of growth, while others point to a static self and world with fixed qualities. These beliefs are part of the motivational system and strongly influence what goals people pursue. The cultivation of children’s growth mindset in family education can help children construct their desired life and study and maintain flexibility. No matter whether things are fulfilled or not, it will inject enthusiastic attempts and efforts into children’s life and study. These attempts and efforts can help children live a determined life, solve problems actively and discover their potential.